0 votes
481 views
in Mathematics Form 3 by

Solve the quadratic equation by completing of squares giving your answer to 3sf     
11x2 –13x+3=0 

1 Answer

0 votes
by

x− 13/11 = −3/11 
x2 −13/11 + (−13/11)2 = −3/11 + (−13/11)2
(x − 13/11)2 = −3/11 169/121
                   =136/121
x − 13/11 =±√136/121
either x = √136/121 13/11
           =11.66 +13 =2.242
                11      11
Or x = −√136/121 + 13/11
           =−11.66 +13 = 0.1218
                       11

Welcome to EasyElimu Questions and Answers, where you can ask questions and receive answers from other members of the community.

6.4k questions

9.6k answers

6 comments

590 users

...